(9x+11)+(9x-5)=

Simple and best practice solution for (9x+11)+(9x-5)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (9x+11)+(9x-5)= equation:


Simplifying
(9x + 11) + (9x + -5) = 0

Reorder the terms:
(11 + 9x) + (9x + -5) = 0

Remove parenthesis around (11 + 9x)
11 + 9x + (9x + -5) = 0

Reorder the terms:
11 + 9x + (-5 + 9x) = 0

Remove parenthesis around (-5 + 9x)
11 + 9x + -5 + 9x = 0

Reorder the terms:
11 + -5 + 9x + 9x = 0

Combine like terms: 11 + -5 = 6
6 + 9x + 9x = 0

Combine like terms: 9x + 9x = 18x
6 + 18x = 0

Solving
6 + 18x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-6' to each side of the equation.
6 + -6 + 18x = 0 + -6

Combine like terms: 6 + -6 = 0
0 + 18x = 0 + -6
18x = 0 + -6

Combine like terms: 0 + -6 = -6
18x = -6

Divide each side by '18'.
x = -0.3333333333

Simplifying
x = -0.3333333333

See similar equations:

| 3x+7x-5=5 | | -7h=42 | | x(2x+2)=600 | | 1.4=x^25 | | 0=625-16x^2 | | 3.7q-5.8-4.5q=-1.8q-5.2 | | y=-18+11 | | y-1.7=-1.8 | | .43x=184.90 | | -8m+27=2m-3 | | B=r+rv*d | | 3x-9x+33=-3 | | f/2=7 | | -(15-3s)-(8s+1)=39 | | 9x^3y+6xy^2=0 | | y=15x-40 | | P(9)=4x+3 | | 20=2l+2w | | -(9-t)=-18 | | P(a+9)= | | 9(x+4)=3x | | 5a^2+25=0 | | 12w=7w+15 | | G(x)=6x-13 | | 4x^2-26x=-3x^2-8x-8 | | =20+15x-6-9x | | 63-b=54 | | 7d-23=12 | | 21+6y=23 | | 1x(4-5)=15 | | -33=5t+7 | | 9+39x+31=4x-3 |

Equations solver categories